The national oceanic and coastal policies in the maritime governance of Ecuador - Vélez Altamirano, David Leonardo (2021)
This article discusses Ecuador's oceanic and coastal policies (PNOC) contribution to maritime governance. The experience in Brazil and Colombia, countries with planned and strategic visions of maritime governance, has been considered. This comparison is key to build a maritime governance model applicable to Ecuador. This paper collects information from current legal regulations in three countries and also reviews relevant secondary sources. The results study show that operational Ecuadorian PNOC policies do not have meaningful incidence within regional and international treaties and, consequently, related government agencies perform poorly. Policies' contribution to Ecuador's maritime governance depends on some actions, particularly at the Executive level, such as greater inter-agency cooperation.